Learnings from rapid response efforts to remotely detect landslides triggered by the August 2021 Nippes earthquake and Tropical Storm Grace in Haiti - Pukar Amatya; Corey Scheip; Aline Déprez; Jean-Philippe Malet; Stephen L. Slaughter; Alexander L. Handwerger; Robert Emberson; Dalia Kirschbaum; Julien Jean-Baptiste; Mong-Han Huang; Marin K. Clark; Dimitrios Zekkos; et al. (Natural Hazards, 2023)
On August 14, 2021, a Mw 7.2 earthquake struck the Tiburon Peninsula of western Haiti triggering thousands of landslides. Three days after the earthquake on August 17, 2021, Tropical Storm Grace crossed shallow waters offshore of southern Haiti triggering more landslides worsening the situation. In the aftermath of these events, several organizations with disaster response capabilities or programs activated to provide information on the location of landslides to first responders on the ground. Utilizing remote sensing to support rapid response, one organization manually mapped initiation point of landslides and three automatically detected landslides. The 2021 Haiti event also provided a unique opportunity to test different automated landslide detection methods that utilized both SAR and optical data in a rapid response scenario where rapid situational awareness was critical. As the methods used are highly replicable, the main goal of this study is to summarize the landslide rapid response products released by the organizations, detection methods, quantify accuracy and provide guidelines on how some of the shortcomings encountered in this effort might be addressed in the future. To support this validation, a manually mapped polygon-based landslide inventory covering the entire affected area was created and is also released through this effort.

Microplastics in the Arctic: a transect through the Barents Sea - H. Emberson-Marl; R. L. Coppock; M. Cole; B. J. Godley; N. Mimpriss; S. E. Nelms; P. K. Lindeque (Frontiers in Marine Science, 2023)
Globally, the abundance of microplastics in our oceans is increasing, including within the remote locations of the polar regions. The Barents Sea, which adjoins the Arctic Ocean, is an area of high primary productivity that, owing to the convergence of regional currents, has been mooted as a potential sixth ocean gyre that may coalesce high concentrations of plastic debris. This study aimed to explore data collected from large volume samples of sub-surface water collected from transects through the Barents Sea to quantify and characterise microplastics in this region, with a focus on potential impacts to zooplankton. Overall, the mean microplastic abundance in the Barents Sea was 0.011 microplastics m -3 (range: 0.007 – 0.015 m -3 ). Microplastics were found in higher abundances nearer land mass at the southern end of the transect and northwards towards the ice edge, recording 0.015 microplastics m -3 during both transect legs. Microplastics were predominantly fibrous (92.1%) and typically blue (79%) or red (17%) in colour. A range of polymers were identified including polyester (3.8%), copolymer blends (2.7%), elastomers (7.1%) and acrylics (10.6%), however semi-synthetic polymers dominated, comprising 74.4% of particles found. Higher microplastic concentrations in the northernmost transect may stem from melting sea-ice, while the higher concentrations in the southernmost transect likely derive from the long-range transport of microplastics via currents from Europe.

Implications of individual variation in insect behavior for host specificity testing in weed biocontrol - Melanie L. Haines; Rowan M. Emberson; Andy Sheppard; Pauline Syrett; Toni M. Withers; Susan P. Worner (BioControl, 2013)

Asynchrony from synchrony: long-range gamma-band neural synchrony accompanies perception of audiovisual speech asynchrony - Sam M. Doesburg; Lauren L. Emberson; Alan Rahi; David Cameron; Lawrence M. Ward (Experimental Brain Research, 2008)

Characteristics of an ozone deposition module II: Sensitivity analysis - D. Simpson; J.-P. Tuovinen; L. Emberson; M. R. Ashmore (Water, Air, & Soil Pollution, 2003)

Modelling and Mapping Ozone Deposition in Europe - L. D. Emberson; M.R. Ashmore; D. Simpson; J.-P. Tuovinen; H.M. Cambridge (Water, Air, & Soil Pollution, 2001)